Information Systems on Environmentally Sound and Appropriate Technologies - Siddappa, H.C.R. (DESIDOC Journal of Library & Information Technology, 2003)
This paper highlights the genesis of lnformation Systems on Environmentally Sound and Appropriate Technologies which is sponsored by Ministry of Environment & Forests, Government of india. A brief profile of Development Alternatives is given. Objectives, potential users, and using new information technologies in lnformation Systems on Environmentally Sound and Appropriate Technologies are mentioned along with the policy of colection of data and information. Brief description of each database created and periodically updated to retrieve data and information to users all over the world is given. Online access to data and information by public from all parts of the world is mentioned by briefly describing DAINET along with future plans. http://dx.doi.org/10.14429/dbit.19.2.3468